The Effect Of Character Education In Stelma Learning On Students' Social Attitudes Class XII - Liber Napitupulu; Sarma Dewi Kemala S; Dame Meldaria Sipahutar (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to determine the Effect of Character Education in Stelma Learning on the Social Attitudes of Grade XII Students at SMAK Stella Maris. The research model that will be used is a quantitative research model and conducting questionnaires and questionnaires that will be carried out through Google forms to SMAK Stella Maris Surabaya students. The author looks for sources from several books and journals from the internet about character education and its influence on the social lives of SMAK Stella Maris Surabaya students. Based on the results of data analysis in chapter IV regarding character education in Stelma Learning on the social attitudes of grade XII students at SMAK Stella Maris, the following conclusions can be drawn: Character education is very important in the formation of student character. Acceptance of character education by students can make it easier for students to live in society. Positive impacts are felt by students when receiving character education at school